Automatic variation plant detector using aquaponic concept / Nur Syahirah Kamarozaman ... [et al.] - Kamarozaman, Nur Syahirah; Md Enzai, Nur Idawati; Mahzan, Norhidayatul Hikmee; Hashim, Shaiful Bakhtiar (2017)
The farmers manually control the irrigation system in agriculture especially in small-scale area. Sometimes it can lead to either inadequate or excessive amount of water supplied to the plant. This project is designed to help in water conservation by watering the plants using aquaponic concept. The aquaponic concept is about growing fish and plant together in one re-circulating system. Since the heat stress and heavy rain can affect the plant growth, thus this project is equipped with the sensors to control the excessive amount of water and heat to the plant. There are three main sensors used in this project, which are soil moisture, rain and heat sensors. The soil moisture sensor circuit diagram controls the watering system for the plant. If the soil gets dry, the fish tank water will be supplied to the plant by using motor/water pump. The rain and heat sensor circuits help to detect excessive water and heat stress to the plant. These circuits will trigger the roof/shelter to shade the plant.